CounterStories from the writing center - Faison, Wonderful; Condon, Frankie (Utah State University Press, 2022)
"Gathers emerging scholars of colour and their white accomplices to challenge the cherished lore about the work of writing centres. Writing within an intersectional feminist frame, the contributors name and critique the dominant role that white, straight, cis-gendered women have played. This will shake the field's core assumptions about itself."--